Intralesion Triamcinolon Injection Therapy on Esophageal Stricture as Side Effect of Long Term Use Biphosphonate - Arles Arles; Yoanda Silvia (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2017)
Systemic Lupus Erythematous (SLE) is a chronic inflammatory disease that affect almost any organ system. Patient with SLE is at risk of osteoporosis. Biphosphonate is one of osteoporosis treatments. However, esophageal stricture (ES) caused by continuous esophageal inflammation as a result of long-term use Biphosphonate can occur. Intralesion Triamcinolone Injection (ITI) becomes one of ES therapy by inhibiting inflammatory response to injury and decrease subsequent collagen formation. ITI inhibits transcription of matrix protein genes, including fibronectin and procollagen. It also reduces the synthesis of  α2-macroglobulin, an inhibitor of collagenase activity. A 43 year old woman was diagnosed with SLE. She was treated with Risedronic Acid (bisphosphonate class) 35 mg once a week. After 8 months, she started complaining difficulty to swallow. Symptom was getting worse 6 months later. One-third distal ES with inflammation process was found with endoscopy. ITI 150 mg was given in inflammation area. She was scheduled to follow up after 7 days for re-endoscopy.  Endoscopy showed that inflammation process had been improved. Six months later, she had again complained difficulty to swallow and we found that she still consumed Risedonic Acid. ITI 150 mg was given because inflammation and ES was found with endoscopy.  After 7 days, endoscopy showed that there was no ES and inflammation process had been improved. She was advised to stop Risedronic Acid consumption.